MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) DALAM MENUMBUHKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PPKN - Nina Marlina; Evi Endriani; Ondih Suhendi; Via Febrianti; Muhamad Subkhan (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Student learning motivation is a key factor in the success of the learning process. Civics and Citizenship Education (PPKn) often faces challenges in maintaining students’ interest and motivation to learn. One method that can be used to enhance learning motivation is Number Head Together (NHT), which encourages active student participation through group discussions. This research intends to explore the influence of implementing the NHT learning method on enhancing students’ learning motivation in PPKn. The research uses a descriptive qualitative approach. Participants are students of class XI IPS at SMA Negeri 1 Karawang. Data were collected through classroom observations, interviews with students, and documentation analysis. The results show that the implementation of the NHT method significantly increases active student participation in learning. Students are actively engaged in group discussions, asking more questions, and experiencing improved understanding of PPKn materials. Furthermore, students’ learning motivation also increases as a result of positive experiences in collaborative learning. The implementation of the NHT learning method can effectively enhance students’ learning motivation in PPKn. This method not only expands students’ knowledge but also helps in developing their social skills through better interaction with teachers and peers.